Active ageing : Voluntary work by older people in Europe - Principi, Andrea (Policy Press, 2014)
'Active ageing' has become a key phrase in discourses about challenges and remedies for demographic ageing and the enrolment of older adults into voluntary work is an important dimension of it. The pattern and factors conditioning volunteering among older people has so far been an under-researched topic in Europe and this is the first book to study volunteering among older people comparatively and comprehensively.